Novel roles for hERG K+ channels in cell proliferation and apoptosis - Jehle, Julian; Schweizer, Patrick Alexander; Katus, Hugo; Thomas, Dierk (Cell death & disease, 2011)
The human ether-a-go-go-related gene potassium channel (hERG, Kv11.1, KCNH2) has an essential role in cardiac action potential repolarization. Electrical dysfunction of the voltage-sensitive ion channel is associated with potentially lethal ventricular arrhythmias in humans. hERG K+ channels are also expressed in a variety of cancer cells where they control cell proliferation and apoptosis. In this review, we discuss molecular mechanisms of hERG-associated cell cycle regulation and cell death. In addition, the significance of hERG K+ channels as future drug target in anticancer therapy is highlighted.